Cell‐penetrable mouse forkhead box protein 3 alleviates experimental arthritis in mice by up‐regulating regulatory T cells. (10th May 2015) - Liu, Xia; Ji, Baoju; Sun, Mengyi; Wu, Weijiang; Huang, Lili; Sun, Aihua; Zong, Yangyong; Xia, Sheng; Shi, Liyun; Qian, Hui; Xu, Wenrong; Shao, Qixiang
Summary: Regulatory T cells (Tregs ) have potential applications in clinical disease therapy, such as autoimmune diseases and transplant rejection. However, their numbers are limited. Forkhead box protein 3 (FoxP3) is a key transcription factor that controls Treg development and function. Here, we generated a cell‐permeable fusion protein, protein transduction domain (PTD)‐conjugated mouse FoxP3 protein (PTD‐mFoxP3), and evaluated whether PTD‐mFoxp3 can alleviate rheumatoid arthritis (RA) in the collagen‐induced arthritis (CIA) mouse model. As expected, PTD‐mFoxP3 was transduced into cells effectively, and inhibited T cell activation and attenuated the cell proliferation. It decreased interleukin (IL) 2 and interferon (IFN)‐γ expression, and increased IL‐10 expression in activated CD4 + CD25 − T cells. PTD‐mFoxP3‐transduced CD4 + CD25 − T cells attenuated proliferation of activated CD4 + CD25 − T cells. In addition, PTD‐mFoxP3 blocked the Th17 differentiation programme in vitro and down‐regulated IL‐17 production from T cells by modulating induction and levels of retinoid‐related orphan receptor gamma t (RORγt). Intra‐articular delivery of PTD‐mFoxP3 delayed disease incidence remarkably and alleviated autoimmune symptoms of CIA mice. Moreover, protective effects of PTD‐mFoxP3 were associated with regulating the balance of T helper type 17 (Th17) and Tregs . These results suggest that PTD‐mFoxP3 may be a candidate for RA therapy.